2002
DOI: 10.1678/rheology.30.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Concentration and Axial Ratio on the Rheological Properties of Cellulose Fiber Suspensions.

Abstract: The steady flow and the dynamic viscoelastic properties of cellulose fiber suspensions were investigated as functions of the suspension concentration and the fiber shape using a parallel-plate type rheometer. Various concentrations of the suspensions were made from various types of cellulose fibers, i.e., microcrystalline cellulose, bacterial cellulose, and fibrillated cellulose fibers. All the suspensions showed non-Newtonian flow even at very low concentrations. The flow property of each suspension showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
83
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 7 publications
17
83
3
1
Order By: Relevance
“…It shows non-Newtonian behaviour when diluted with water at low concentrations, independent to angular frequency. Furthermore, magnitude of its dynamic storage reaches plateau condition in relative high concentrations with storage moduli bigger than ten times than the loss moduli [8][9]. As reported in other research, the treatment using sonication process can altered the morphology structure and tensile modulus of these cellulose solutions.…”
Section: Introductionsupporting
confidence: 55%
“…It shows non-Newtonian behaviour when diluted with water at low concentrations, independent to angular frequency. Furthermore, magnitude of its dynamic storage reaches plateau condition in relative high concentrations with storage moduli bigger than ten times than the loss moduli [8][9]. As reported in other research, the treatment using sonication process can altered the morphology structure and tensile modulus of these cellulose solutions.…”
Section: Introductionsupporting
confidence: 55%
“…[24][25][26][27][28][29][30] According to these reports, a power law correlation was found between the plateau modulus G¢ and the volume concentration c v , namely, G¢¼k c v a where k and a are parameters that are independent of c v . Tatsumi et al 29,30 have also explained that the k is the index of fiber flexibility, which depends on Young's modulus and the aspect ratio of the fiber. The result of the investigation of the plateau modulus and the content of VGCF in Figure 3 was that log G¢ was proportional to log c v of VGCF-s in the PC-L/VGCF-s system.…”
Section: Effect Of Pc Matrix Viscosity J Nithikarnjanatharn Et Almentioning
confidence: 99%
“…The same researchers have also obtained the mathematical relationship between the modulus and concentration in a pulp fiber suspension system. [25][26][27][28][29] Tatsumi 30 has reported that the elastic modulus and the concentration of the pulp fiber are related by a power law. On the basis of the polymer gel solution system, Tatsumi has also reported that a power law could be theoretically expressed in the microfiber suspension system.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of fiber suspensions to form networks that help transmit stresses, in addition to the flocculation phenomena, among other factors, results in a non-Newtonian behavior (Kerekes 2006;Bousfield 2008;Derakhshandeh et al 2011), exhibiting viscoelastic properties. This has practical implications in many stages of the papermaking and bioconversion processes, e.g., during the transport of fiber suspensions, the forming of paper (Tatsumi et al 2002), and mixing of biomass slurries (Nutsen and Liberatore 2009). Therefore, is then of crucial interest to know the rheology of bagasse suspensions to ensure optimal process implementation and the right selection of equipment.…”
Section: Introductionmentioning
confidence: 99%